Efficiency of surgical treatment of neovascular glaucoma: a retrospective analysis - A. V. Zolotarev; E. V. Karlova; M. V. Radaikina; A. A. Kuz'mina; O. V. Ryzhkova (Российский офтальмологический журнал, 2023)
Purpose: to compare the results of neovascular glaucoma (NVG) surgery of patients treated for the underlying eye disease with antiVEGF therapy and laser coagulation (LC) of the retina with the surgery results of patients who did not receive underlying disease treatment.Materials and methods. A retrospective analysis of case histories and outpatient charts of 70 patients (70 eyes) with NVG, operated in a surgical hospital, involved two groups of patients: group 1 — 33 eyes of patients treated for the underlying disease with anti-VEGF therapy and/or LC; of these, 13 eyes (39 %) received panretinal LC, 15 eyes (45 %) received an anti-VEGF drug intravitreally, and 5 eyes (16 %) received both anti-VEGF therapy and LC); group 2 — 37 eyes of patients not treated for the underlying disease. In group 1, NVG was caused by diabetic retinopathy (DR), which accounted for 19 eyes (57.6 %), and post-thrombotic retinopathy (PR) — 14 eyes (42.3 %). IOP data in group 1 at admission was 38.00 ± 6.82 mm Hg. In group 2, the proportion of patients with DR was 32 % (12 eyes), and those with PR — 41 % (15 eyes). The level of IOP in group 1 upon hospital admission was 38.00 ± 6.82 mm Hg, while in group 2 it was 35.97 ± 5.85 mm Hg.Results. In group 1, in most cases, the classical surgical approach to NVG treatment was used. The proportion of Ahmed drainage implantations was 46 % (15 eyes), trabeculectomy (TET) — 24 % (8 eyes), non-penetrating sinustrabeculectomy (NST) — 6 % (2 eyes), and only 24 % (8 eyes) received transscleral cyclophotocoagulation (CPC). After 7 days, the average level of IOP in group 1 was 16.80 ± 7.18 mm Hg, after 1 month, 19.50 ± 3.45 mm Hg, after 3 months, 21.80 ± 3.15 mm Hg, and after 6 months — 22.57 ± 3.34 mm Hg (p < 0.05). In group 2, the operation of choice was CFC, which was performed in 46 % (17 eyes), the Ahmed drainage was implanted less often — 36 % (13 eyes), while 18 % (7 eyes) accounted for TET. The IOP level in group 2 after 7 days was 20.00 ± 8.74 mm Hg, after 1 month, 25.30 ± 4.67 mm Hg, after 3 months 28.43 ± 6.54 mm Hg, and after 6 months 29.73 ± 4.18 mm Hg (p < 0.05).Conclusion. The timely treatment of the underlying disease with Anti-VEGF and LC of the retina allows the patient to maintain visual functions, and increases the effectiveness of NVG surgery.